2017
DOI: 10.1016/j.jchemneu.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of motor neuron differentiation potential of human umbilical cord blood- derived mesenchymal stem cells, in vitro

Abstract: Many people suffer from spinal cord injuries annually. These deficits usually threaten the quality of life of patients. As a postpartum medically waste product, human Umbilical Cord Blood (UCB) is a rich source of stem cells with self- renewal properties and neural differentiation capacity which made it useful in regenerative medicine. Since there is no report on potential of human umbilical cord blood-derived mesenchymal stem cells into motor neurons, we set out to evaluate the differentiation properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…MSC-MNs, however, have only been poorly characterized, and concerns exist over whether MSCs can be differentiated into mature MNs. Some studies seem to have succeeded in generating MNs from MSCs, but these are not always confirmed with electrophysiology, purity analysis, synapse-formation, or spinal grafting (Faghihi et al, 2015; Darvishi et al, 2017; Yousefi et al, 2017). For these reasons, ESC and iPSC MNs may hold greater clinical potential than MSC MN-like cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSC-MNs, however, have only been poorly characterized, and concerns exist over whether MSCs can be differentiated into mature MNs. Some studies seem to have succeeded in generating MNs from MSCs, but these are not always confirmed with electrophysiology, purity analysis, synapse-formation, or spinal grafting (Faghihi et al, 2015; Darvishi et al, 2017; Yousefi et al, 2017). For these reasons, ESC and iPSC MNs may hold greater clinical potential than MSC MN-like cells.…”
Section: Methodsmentioning
confidence: 99%
“…However, ESCs raise ethical and immunogenic concerns. Mesenchymal stem cells (MSCs) have also been shown to differentiate into MNs, using cells harvested from bone marrow (Ma et al, 2011; Faghihi et al, 2015), umbilical cord blood (Yousefi et al, 2017), and adipose tissue (Darvishi et al, 2017). However, MSC transplants have been found to yield inconsistent results (Gowing and Svendsen, 2011; Oliveri et al, 2014; Qu and Zhang, 2017) and mature MSC-MN subtypes are not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Human umbilical cord blood-derived MSCs differentiated into motor neurons after the exposure to retinoic acid (RA), sonic hedgehog (Shh), and brain-derived neurotrophic factor (BDNF) using a three-step in vitro procedure. Cells showed a bipolar morphology and expressed markers associated to motor neurons [28]. BMMSCs can be differentiated in functional motor neuron-like cells using β -mercaptoethanol, RA, Shh, and nerve growth factor (NGF) [29].…”
Section: Mesenchymal Stem Cell Characteristicsmentioning
confidence: 99%
“…Placental tissues have been extensively investigated with regard to their role in facilitating neurologic recovery given their neurotrophic capabilities. 1214,3739,44 AECs and umbilical cord tissue and cord blood have been particular targets in this line of research. In vivo animal models have shown that AECs can promote neural cell differentiation, 65 reduce secondary neural damage associated with inflammation and apoptosis associated with SCI, 66 modulate spinal cord microglia activity to suppress mechanical allodynia, 67 promote remyelination of nerve fibers and promote sprouting of nerve fibers, 68 and improve functional recovery.…”
Section: Methodsmentioning
confidence: 99%
“…43 In addition, umbilical cord blood has also shown potent production of motor-neuron-related markers, making it a prime target for motor nerve regeneration research. 44 …”
Section: Placental Tissuementioning
confidence: 99%